2015
DOI: 10.3329/ajmbr.v1i1.25499
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infectious bursal disease in broiler birds of three districts in Bangladesh

Abstract: A cross-sectional study was conducted in 450 broiler farms of three districts of Bangladesh from June 2012 to July 2013. The estimated prevalence and mortality of infectious bursal disease (IBD) in three districts were 10.2% (CI, 9.2-11.2) and 7.8% (CI, 6.4-9.2) respectively. On clinical sign such as anorexia, ruffled feathers and diarrhoea and necropsy gross changes at bursa of fabricius, the highest prevalence was recorded in Comilla district (10.4%) followed by Feni district (10.3%) and Chittagong district … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The prevalence of IBD was significantly higher in broiler chickens which agreed with several previous findings Das et al, 2018). The prevalence was higher between the age of 11 and 35 days which is congruent with the earlier published research articles (Chakma, 2015;Islam et al, 2016;Hassan et al, 2016;Rahman et al, 2019). Initial 2 weeks of ages, chicks get maternally derived antibody from mother, after that proper vaccination should be ensured to protect from IBD (Rashid et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The prevalence of IBD was significantly higher in broiler chickens which agreed with several previous findings Das et al, 2018). The prevalence was higher between the age of 11 and 35 days which is congruent with the earlier published research articles (Chakma, 2015;Islam et al, 2016;Hassan et al, 2016;Rahman et al, 2019). Initial 2 weeks of ages, chicks get maternally derived antibody from mother, after that proper vaccination should be ensured to protect from IBD (Rashid et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…It is noted that about 30% of total chickens in Bangladesh die due to several disease outbreak (Badruzzaman et al, 2015). Poultry diseases thrive due to several factors such as climate, geographical position, farm hygiene, biosecurity, immunity status, chick quality, hatcheries, and management practices (Abbas et al, 2015;Badruzzaman et al, 2015;Chakma, 2015;Hassan et al, 2016). Along with species of chickens, production type, age and sex play significant role in disease prevalence (Yunus et al, 2009;Rashid et al, 2013;Talukder et al, 2017;Rahman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery by Cosgrove (1962), infectious bursal disease (IBD), caused by infectious bursal disease virus (IBDV), has continued to plague the poultry industry worldwide. The disease is acute, highly contagious and affects chickens aged 3-6 weeks, causing severe immunosuppression in infected chickens below 3 weeks of age (Chakman, 2015). Though, evidences of outbreaks in older chickens have been documented (Okoye and Uzoukwu, 1981;Shekaro and Josiah, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The endemicity of IBD among viral diseases of chickens in Maiduguri (with Newcastle disease) in 1995-2000 was previously reported; the viral diseases were 69.9% of all disease outbreaks in chicken farms(Ambali et al, 2003).Our data showed that IBD outbreaks occurred more frequently among Noiler chickens (25.0%) and exotic cockerels (17.5%) than broilers (7.2%), layers (7.2%) and the local or village chickens (9.1%), indicating that chicken type signi cantly affected outbreak prevalence. The lighter breeds of chicken are reported to be more susceptible to IBD than the heavy breeds; layers are affected more than broilers(Okoye et al, 1999;, 2010;Chakma, 2015;Kundu et 2018) since the chickens would be protected by maternal antibodies against IBDV; however, lack of maternal antibodies could reduce the age of chickens susceptible to the disease, in contrast to the highest susceptibility to IBDV infection at 4-5 weeks of age when maternal antibodies, available from day old have decayed with age(Panisup et al, 1984). Most IBD outbreaks were reported at 3-5 weeks(Mbuko et al., 2010), 3-4 weeks (Mor et al, 2010; Chakma, 2015; Kundu et al, 2018), or 3-6 weeks…”
mentioning
confidence: 99%